Evaluación de las variables del comportamiento organizacional a nivel grupal en la empresa FishCorp. - Sabando Vera, Gema Victoria (2018)
The main objective of this research was to evaluate the variables of organizational behavior at the group level for the contribution of managerial decision-making in the tuna company Fishcorp, canton Jaramijó, which was developed through four phases, beginning in the search for bibliographic information regarding topics related to research; Then the organizational competencies of the tuna industries of Manabí were determined through the Delphi method, which consisted of the consultation of experts in the subject, thus establishing the respective constructs based on the characteristics of the tuna sector. In such a way that we continued to evaluate the CO variables at the group level, considering a total of 4 variables by departments according to the Kendall result and for the execution techniques such as observation, interview and survey were applied, obtaining relevant data, besides using the program of Microsoft Excel to process the answers of the respondents and through the tabular statistics the information and analyze the graphs, establishing the deficiencies with greater level of influence on the variables studied and indicating the department in which they presented with more frequency. Later on, in an Ishikawa, to show the causes and sub-causes that fed the central problem, that is, the performance of the Fishcorp working groups, from which it was possible to identify the competences with which each department was related, guiding the action plan represented in the 5W1H matrix to contribute to the improvement of managerial decision making in the company.